RANCANG BANGUN SISTEM INFORMASI SIMPAN PINJAM BERBASIS WEB PADA KOPERASI UNIT DESA SOLIAMITRA DEPOK - Ibnu Rusdi; Ade Sri Mulyani; Diah Winiasti Telaumbanua; Rini Kusuma Wardani (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2020)
The Industrial Era 4.0 is now very rapid with the development of all forms of digital applications to record all transactions that are running. Koperasi Unit Desa (KUD) Soliamitra requires a system in the running business process because the savings system itself uses a desktop-based or computerized system, but when the loan process is still done manually, using Microsoft Excel starting from applying for loans, installment payments to storage data relating to lending to report preparation, so that when recording loan data there are still frequent recording errors, using the web-based savings and loan information system technology is expected to improve service performance for members of the Koperasi Unit Desa (KUD) Soliamitra. In making this information system the author uses the SDLC method with a waterfall model, because step by step can be completed in an ordered and structured manner, and the design drawings using Unified Modeling Language (UML) as analysis and design and using NetBeans software for system implementation Java Servlet based object to support Web Application.